Repentance And The Responsibility Of Holy Living For Believers - Allen Pangaribuan; Vera SM Simanjuntak; Piter Imanson Damanik; Amoli Ndraha (International Journal of Christian Education and Philosophical Inquiry, 2024)
Repentance is needed because humans realize that they are sinners. Sinful people must be saved through repentance, without repentance sinful humans cannot be saved. Thus repentance has a strong connection with the salvation of believers. Salvation in the concept of the Old Testament people was to turn around and live in God's law. If they repent and obey, they will be saved, that is, they will be blessed with physical blessings such as victory over war, successful harvests, and being able to perform worship. On the other hand, if they do not repent of their sins, they will be condemned or cursed by God. This understanding of repentance and salvation has been adopted by adherents of prosperity theology. They say that Christians who have had their sins forgiven through repentance will be saved and live abundantly with physical blessings, success and prosperity. For the New Testament people, the goal of repentance and salvation is to achieve physical blessings like the Old Testament people or adherents of prosperity theology. This research tries to research and find the correct understanding of repentance and salvation which has implications for the responsibility of believers to maintain the holiness of their lives every day because humans are the holy image of God on this earth. The aim of this research is to find the true understanding of repentance and salvation in Christianity which has implications for the responsibility of Christians to live without falling into sin again or to live in the morality of God's holy holiness. The research in this paper uses a qualitative approach with the technique of writing a literature review or literature study. The research results show that the understanding of repentance and salvation to achieve the image of God who is in the image and likeness of God has implications for the responsibility of the congregation to achieve the morality of holiness like God. This research also shows that repentance is the renewal of the mind until it has thoughts and feelings like Christ. This research also found that the notion of repentance and salvation only by God's grace alone on the basis of damage to God's image in humans based on God's absolute sovereignty has no implications for the believer's responsibility to strive to live without sin or without blemish. Repentance is completely a gift where humans cannot exercise their free will to choose so that believers are not required to take a proportional responsibility to change their character based on individual decisions in order to live a holy life. Repentance in Christianity is no longer focused on physical blessings but on the restoration of God's image with the responsibility of the believer's holy life